PRINSIP KOOPERATIF, KESANTUNAN, DAN PARAMATER PRAGMATIK DALAM WACANA HUMOR GUS DUR - Jupriono, D. (TANDA, 2023)
This research discusses the verbal humour of Gus Dur from the perspective of speech acts (cooperative principle, politeness principle and pragmatic parameter). With qualitative approach and constructivistic paradigm, this study applies the strategy of text ethnography. By referential identity method and documentation, selection, classification and explanation technique, finally it is known that in the verbal humour of Gus Dur, there are always deviations on the cooperative principle (maxim of quantity, quality, relevance and manner), the politeness principle (tact, generosity, approbation, modesty, agreement, and sympathy maxim), and pragmatic parameter (distance, power, and rank rating).